Coinfección por dengue y leptospirosis en una niña de la Amazonía Peruana - Núñez Garbín, Alexandra (2015)
We report the case of a 10 year old girl, born and raised in the city of Iquitos in Peru who presented with headache, fever, chills, musculoskeletal pain, mild epigastric pain, epistaxis and hematemesis. On physical examination, the patient was afebrile and in good general condition. Serological tests confirmed infection of dengue and leptospirosis. The patient received intravenous hydration with sodium chloride 0.9% and penicillin G sodium, achieving a favorable clinical course such that she was discharged a few days after admission to the hospital. Although these diseases are common in the Peruvian Amazon, the simultaneous presence of both in the pediatric population is little documented; therefore, a good clinical history and laboratory tests are important for diagnosis and treatment.